Smallholder’s Readiness to Adopt Platforms Linking Local Resource-Sharing in Egypt - Pham, Congduc; Mansour, Tamer Gamal Ibrahim; Lionboui, Hayat; Fawzy, Zakaria Fouad; Shairra, Souad A.; Awad, Nahla A.; El-Gamal, Seham Mohamed Abd El Hameed (Journal of Ecohumanism, 2025)
Digital technology in developing countries improves agriculture with knowledge and experience. Digital platforms can link local resource-sharing networks to connect agricultural sectors, especially in emergencies. Hence, this paper assessed smallholders’ readiness to adopt platforms facilitating local link resource-sharing in Egypt. This was achieved by assessing the existing options for resource sharing and identifying the factors that influence this sharing, evaluating the respondents’ understanding of information and communication technology (ICT) identifying their sources of information about these tools, and determining the reasons behind the respondents’ use of digital platforms. A structured questionnaire was administered to 128 selected farmers from Beni Suef Governorate in Egypt. The results showed that work (65.5%) and agricultural operations (irrigation-fertilization-harvesting) (62.5%) were the most important present possibilities for sharing resources. As were their agricultural uses, ICTs and the Internet of Things (IoT) were unfamiliar to 53.88% of respondents. Using information digital platforms in agriculture was crucial for finding new markets (84.4%), increasing productivity (81.25%), and increasing profitability (78.13%). at the same time, 81.25% of respondents cited a lack of awareness about new digital application technologies as a major barrier to embracing digital platforms in agriculture. Thus, the study recommends the importance of moving forward toward establishing the RESILIENCE platform with farmers and considering their participation at every project stage.